Thermodynamical model for hydrogen storage capacity in carbon nanostructures. (22nd March 2015) - Avdeenkov, A.V.; Bodrenko, I.V.; Bessarabov, D.G.; Bibikov, A.V.; Nikolaev, A.V.; Taran, M.D.; Tokarev, A.; Tkalya, E.V.
Abstract: A simple thermodynamical model taking into account non-ideality and inhomogeneity of absorbed hydrogen molecular gas has been proposed to calculate hydrogen storage capacity in carbon nanostructures as a function of temperature and pressure. The model utilizing the effective interaction potential of the hydrogen molecule with the atoms of the considered material, is based on the experimental equation of state and a local density approximation for molecular hydrogen. We have applied the model for the search of the optimal geometry for hydrogen storage of such promising carbon materials as a set of graphene layers and bundles of carbon nanotubes. We demonstrate that the hydrogen storage capacity depends on the geometry of material and discuss the origin of this effect. Highlights: A simple thermodynamical model for calculations of a hydrogen storage capacity in nanostructures. The model accounts for non-ideality and inhomogeneity of the absorbed hydrogen molecular gas. Generalization of the barometric formula for the non-ideal gas.